Didactic toy for children with special needs - Salgado, João (2020)
In the last years, technology is receiving an important role in the development of new games and toys for children with special needs. In this paper a configurable prototype game is presented specially designed for children with special needs. The goal is to promote reaction and memory skills as well cooperative work in these children. The toy is capable of producing audio and visual sensations and it has more than one playable game (a reaction game, a memory game and a multiplayer game). Furthermore, it is an important tool for the therapists, since all gaming plays are tracked and registered in a database to posteriorly being filtered and presented using statistic methodologies. Preliminary tests were performed in real environment with children mainly with cerebral palsy. The feedback is promising enough to take it to the next step, which will be the integration of artificial intelligence approaches.